Burundi : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper describes economic developments in Burundi during 1993-97. The external current account (excluding grants) narrowed significantly during 1993-95, owing mainly to strong international export prices for coffee and subdued demand for imports. This trend continued in 1996 with a further compression of imports stemming from a sharp reduction in project aid and the economic embargo. The overall balance of payments shifted from a surplus of 0.2 percent of GDP in 1995 to a deficit of 7.3 percent mainly as a result of a sharp drop in external financial assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet